The Modes of Entry of DM-Drogerie Markt into the Turkish Market - Abbasov, Rahman; Halík, Jaroslav, 1961-; Šípková, Martina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
In my thesis, main idea is choosing appropriate mode of entry into Turkish market for the name of DM Drogerie markt. In order to interpret the best conclusion, I used factors, selection process, some strategies, modes of entries, about DM and its market position, PEST, SWOT and some more methots.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses